Development of Pteridophyta E-Teaching Materials In The Bantarbolang Natural Reserve Whit A Scientific Approach To Train Critical Thinking Skills - Bayu, Bagus Adi; Rahayuningsih, Margareta; Irsadi, Andin (Journal of Innovative Science Education, 2023)
Bantarbolang Nature Reserve as a conservation area has not been widely recognized, and has not been utilized in learning. Students also need learning that can train critical thinking skills. The aim of the research is to analyze the diversity of pteridophyta in the Bantarbolang Nature Reserve, to analyze the characteristics, validity and effectiveness of the E-peteridophyta teaching materials in training students' thinking skills. This research is Research and Development (R&D) using 4D model swhich includes four stages, that is Define, Design, Develop, and Disseminate. The results of the study showed (1) Diversity of Pteridophyta in the Bantarbolang Nature Reserve, whichfound 14 species of ferns, from 6 different families. The diversity of ecosystems in the Bantarbolang Nature Reserve, there are River Ecosystems, Forests and Teak Forests. (2) The characteristics of the Pteridophyta E-Materials in the Bantarbolang Nature Reserve have advantages, such as providing contextual examples of images, presented by collaborating between scientific approaches and process skills, and displayed in electronic form which makes it easy to use. (3) The validity of the Pteridophyta E-teaching materials in the Bantarbolang Nature Reserve, obtained an assessment score from material experts of 94.38% so that it is included in the very valid category, and an assessment score from media experts of 98.30% so that it is included in the very valid category. (4) The effectiveness of E-teaching materials on students' critical thinking skills obtains an N-gain score of 0.70, which means the high category, and obtained an Effect size score of 0.49, which means the medium category, thus showing effective results on critical thinking skills with the application of E - Teaching materials.